"It Hurts as If…": Pain-Associated Language, Visual Characterization, and Storytelling in Hmong Adults. Issue 8 (1st November 2019) - Lor, Maichou; Vang, Xia; Rabago, David; Brown, Roger L; Backonja, Miroslav
Abstract: Objective: Pain is challenging to diagnose and manage in primary care, especially when patients have limited English proficiency (LEP). Little is known about whether LEP patients can provide pain information that is consistent with the process and the content that providers expect in a clinical interaction. We explore how LEP Hmong patients communicate their pain to providers in primary care settings. Methods: A qualitative study with 67 Hmong participants (63% female and x̄ age = 53.7 years) were recruited from a Midwestern state. Semistructured interviews on pain communication were conducted, audio-recorded, transcribed, and analyzed using directed content analysis. Results: The Hmong participants described pain using stories that generally had the same dimensions of information that providers require for pain assessment. These included references to time, causality, associated symptoms or related experiences, intensity, and consequences of pain. However, the participants expressed some pain dimensions in language that was not shared by providers: visual metaphors that were generally in reference to pain quality and fewer words for pain location, intensity, and some qualities. Participants used two strategies to decide whether they should tell their pain story: assessing the provider and determining whether their story was appreciated. The perception that providers underappreciated their stories resulted in dissatisfaction and undertreatment of pain. Ultimately, this resulted in having less frequent contact with providers or changing providers. Conclusions: Findings demonstrate a discordance in the expected process and content of the clinical interaction between LEP Hmong patients and providers, suggesting the need for culturally appropriate pain assessments in this population.